The Relationship between Verbal Abuse and Anxiety in Young Adult Women in Dating Relationships - Hana Rahadatul Aisy; Onny Fransinata Anggara (Publikasi Indonesia, 2025)
Verbal abuse in dating relationships is often overlooked and considered a normal conflict, even though it can have a significant impact on mental health, especially in young adult women who are in a vulnerable stage of development. This study aims to analyze the relationship between verbal abuse and anxiety levels in young adult women in dating relationships. The study used a correlational quantitative design with 155 participants aged 18–25 years in Surabaya who had experienced verbal abuse from their partners. The instruments used were the Conflict Tactics Scale 2 (CTS2) to measure verbal abuse and the Beck Anxiety Inventory (BAI) to measure anxiety. The data were analyzed using Pearson's correlation test with the help of JASP software. The results showed a significant positive relationship between verbal abuse and anxiety levels (r = 0.855, p <.001), which means that the higher the experience of verbal abuse, the higher the level of anxiety experienced. These findings reinforce emotion regulation theory and attachment theory, which state that negative interpersonal experiences can disrupt emotion regulation and reinforce anxious attachment patterns, leading to increased anxiety symptoms. In conclusion, verbal abuse in dating relationships has serious implications for mental health, requiring preventive interventions and counseling that emphasize strengthening emotion regulation and healthy relationship literacy.